Electronic Health Record Use Among American Neurotology Society Members. Issue 9 (October 2018) - Kamil, Rebecca J.; Giddings, Neil; Hoffer, Michael; Ying, Yu-Lan Mary; Kwartler, Jed; Brookler, Kenneth; Arriaga, Moises; Agrawal, Yuri
Abstract : Objective: To describe the use of electronic health records (EHR) among members of the American Neurotology Society (ANS). Study Design: Cross-sectional. Setting: Active ANS members in November 2017. Intervention: Internet-based survey. Main Outcome Measure: Survey that assessed the use of EHR in practice, types of EHR programs, different elements of EHR employed, and respondents' satisfaction and efficiency with EHR. Results: One hundred twenty-seven ANS members responded to the survey with 67 (52.8%) respondents working in academic practice and 60 (47.2%) respondents working in private practice. Epic was the most commonly used EHR with 89 (70.1%) respondents using this system. Among all respondents, 84 (66.1%) respondents reported their efficiency was reduced by EHR use, and there was an even split between respondents who reported they were satisfied versus dissatisfied with their EHR (∼40% each). We found that younger members were more likely to feel EHR increased their efficiency compared with the older members ( p  = 0.04). In all other analyses, we found no significant difference in efficiency and satisfaction between age groups, practice settings, presence of residents or fellows, or specific EHR used. The main challenges reported by ANS members related to the EHR were increased time burden, poor user interface, lack of customizability, and the focus away from patients. Conclusions: The majority of ANS members felt their efficiency decreased as a result of EHR. These findings provide specific changes to the EHR that would improve efficiency and satisfaction among neurotologists.